Sacral neuromodulation for low anterior resection syndrome: current status—a systematic review and meta-analysis - Pires, Marco; Severo, Milton; Lopes, Ana; Neves, Sílvia; Matzel, Klaus; Povo, Ana (International Journal of Colorectal Disease, 2023)
Introduction: It is estimated that approximately 70% of patients with rectal cancer who undergo surgery will suffer from Low Anterior Resection Syndrome (LARS). In the last decades, sacral neuromodulation (SNM) has been widely used in urinary dysfunction and in faecal incontinence refractory to medical treatment. Its application in LARS has been investigated and has shown promising results. The paper’s aim is to present a systematic review and meta-analysis of the available literature and evaluate the therapeutic success of SNM in patients with LARS. Methods: A systematic search was performed in international health-related databases: Cochrane Library, EMBASE, PubMed and SciELO. No restrictions on year of publication or language were applied. Retrieved articles were screened and selected according to set inclusion criteria. Data items were collected and processed for each included article and a meta-analysis was done according to the PRISMA guidelines. The primary outcome was the number of successful definitive SNM implants. Further outcomes included changes in bowel habits, incontinence scores, quality of life scores, anorectal manometry data and complications. Results: A total of 18 studies were included, with 164 patients being submitted to percutaneous nerve evaluation (PNE) with 91% responding successfully. During follow-up of therapeutic SNM some devices were explanted. The final clinical success rate was 77% after permanent implant. Other outcomes, such as the frequency of incontinent episodes, faecal incontinence scores, quality of life scores were overall improved after SNM. The meta-analysis showed a decrease in 10.11 incontinent episodes/week; a decrease of 9.86 points in the Wexner score and an increase in quality of life of 1.56 (pooled estimate). Changes in anorectal manometry were inconsistent. Local infection was the most common post-operative complication, followed by pain, mechanical issues, loss of efficacy and haematoma. Discussion/conclusion: This is the largest systematic review and meta-analysis concerning the use of SNM in LARS patients. The findings support the available evidence that sacral neuromodulation can be effective in the treatment of LARS, with significant improvement in total incontinent episodes and patients´ quality of life.
CRIS-Team Scopus Importer:2023-07-21
Keywords: Faecal incontinence (FI); Low anterior resection syndrome (LARS); Meta-analysis; Rectal cancer; Sacral nerve stimulation (SNS); Sacral neuromodulation (SNM)